Optimizing Water and Nitrogen Application to Furrow-Irrigated Summer Corn Using the AquaCrop Model - Yifei Zhao; Shunsheng Wang; Aili Wang (Agronomy)
Summer maize is an important grain crop in the North China Plain, but the problem of irrational application of water and fertilizer is becoming increasingly serious. Optimizing water and nitrogen management not only improves yield but also reduces water and fertilizer waste and environmental pollution. The Aquacrop model was calibrated and validated using a two-year summer maize field trial, and 16 different water and nitrogen scenarios were simulated and analyzed. In particular, the field trials were divided into 10 water–nitrogen treatments. The results showed that (1) the model has good applicability to the growth process of summer maize in the North China Plain. (2) Excessive water and nitrogen application would reduce yield by 5.6–33.7%, nitrogen bias productivity by 8.1–32.5%, and water use efficiency by 6.4–84.6%. (3) The optimal irrigation and nitrogen application program for furrow-irrigated summer maize is an irrigation quota of 360 mm in conjunction with nitrogen application of 240 kg/ha. This study provides a theoretical basis for a water-saving, fertilizer-saving, high-yield water and fertilizer management system for summer maize in the North China Plain.